Proses Penalaran Matematis dalam Menyelesaikan Masalah Matematika Berdasarkan Tipe Kepribadian pada Siswa SMK Kehutanan Negeri Makassar - Nurdyanti Suaedy (Jurnal Studi Guru dan Pembelajaran, 2021)
This study aims to describe the students' mathematical reasoning process in solving mathematical problems in terms of extrovert and introvert personality types. The type of research is descriptive research with a qualitative approach with the instrument in this study is the researcher himself as the main instrument guided by the EPI test, mathematical problem solving test and valid and reliable interview guidelines. The research subjects were students of class XI TIPH consisting of 2 students of type extrovert personality type personality (SE) and 2 students introvert personality type (SI). Data was collected by means of test analysis and interviews. The results showed: the mathematical reasoning process was revealed through mathematical problem solving tasks where all research subjects went through all stages of the mathematical reasoning process. SE comments on their feelings and compares reactions to their experiences based on problems by presenting information in an orderly and random manner and the flow of reasoning, namely synthesizing, analyzing, then generalizing. Furthermore, SI comments on their feelings and compares reactions to their experiences based on problems by presenting information in order and detail as well as the flow of reasoning, namely analyzing, synthesizing, analyzing, then generalizing. draw conclusions on the solutions obtained from mathematical phenomena.